Report of the Fuel Policy Committee - Planning Commission (Planning Commission, 1974)
The Committee was originally required to submit its Report within 12 months but due to delays in obtaining staff for the Committee’s work and in the appointment of a Chairman after the resignation of Shri R. Venkatraman, the Committee could start its work in earnest only in the latter half of 1971. Since it was felt that the Committee’s studies would take time and investment decisions had to be taken urgently by the Government with regard to the Fifth Plan programme in the energy sector, a quick study was made of the "Fuel Policy for the Seventies" and Part I of the Committee’s Report covering the period upto 1978-79 was submitted to Government in May 1972.
Ministry of Petroleum and Chemicals and Mines and Metals
Planning Commission